Estimates of economic values for important traits of two indigenous sheep breeds of Ethiopia - Tadel Gebre, Khasa (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2009)
A bio-economic model based on a deterministic approach was adapted to estimate economic values for important traits of Menz and Horro which are indigenous sheep breeds of Ethiopia. A meat sheep with lamb fattening and rearing of young sheep for replacement was modeled. Traits considered were fattening (daily gain), live weight (ewe mature live weight) and functional traits (length of productive life, lambing interval, and litter size, stillbirth and lamb survival). Economic values were derived independently to avoid double counting and economic values were obtained (in €) per ewe place and year and genetic standard deviation. Negative economic values for length of productive life and ewe mature live weight were obtained for both breeds. For Menz, economic values per genetic standard deviation were 0.63 (daily gain), -0.77 (mature ewe live weight), -0.97 (length of productive life), 1.57 (lambing interval), 0.98 (litter size), 0.41 (stillbirth) and 2.20 (lamb survival). Furthermore, economic values of 1.35 (daily gain), -1.26 (mature ewe live weight), -1.15 (length of productive life), 1.98 (lambing interval), 3.67 (litter size), 0.56 (stillbirth) and 3.25 (lamb survival) were achieved for Horro. Setting economic values of length of productive life and mature ewe live weight to zero, relative economic values for the trait complexes (in %) fattening: functional were 11 : 89 and 12.5 : 87.5 for Menz and Horro sheep, respectively. Economic values for litter size, lambing interval and lamb survival were sensitive to Changes of prices of breeding rams in both breeds.